AS FEIAS (E OS FEIOS) QUE ME DESCULPEM, MAS BELEZA É FUNDAMENTAL : O USO CONTEMPORÂNEO DA IMAGEM E SUA INFLUÊNCIA NA MUDANÇA DOS PARADIGMAS ESTÉTICOS UTILIZADOS NA MÚSICA GOSPEL NO BRASIL - Silva, João Marcos da (2010)
This paper analyzes sociologically in contemporary times the imagery field in gospel music and how it influences the changes of imagery-esthetic paradigms used by phonogram producers in their religious marketing to the commercialization of gospel music in the Brazilian evangelical music market, making it possible in this current model to enable a qualitative and quantitative increase of products aimed at the evangelical public. The research identifies in the dissemination of visual production and marketing of CDs, DVDs, websites of phonogram producers, fairs and music awards, the mechanisms used for the construction of a new imagery paradigm that provides, in the religious field, the emergence of a new evangelical imaginariness mimetically constructed to feed a gospel market supported by the social triad: spectacle, consumption and entertainment. Thus, the analysis has its cut in the paradigmatic changes that arise from the first singers of the 1950s culminating in the explosion of gospel music in the early 1990s.